Highly oil-proof and water-proof fluorine-containing composition and application thereof in coating
By using high oil-resistant and water-resistant fluorine-containing compositions in the coating, including fluorinated hydroxyl acrylic resin, polyurethane acrylate, modified titanium dioxide filler and modified glass flakes, a stable composite structure is formed, and the problem of poor oil-resistant and waterproofing performance of the existing coating is solved, and the excellent water-resistant and oil-resistant performance and mechanical strength of the coating are achieved.
Patent Information
- Application Number
- CN202411691759.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Existing superhydrophobic coatings have poor oil-proof and waterproof performance, resulting in reduced corrosion resistance.
Using a high oil-resistant, water-resistant fluorine-containing composition, including fluorinated hydroxyacrylic resin, polyurethane acrylate, modified titanium dioxide filler and modified glass flakes, a stable composite structure is formed through chemical bonding and physical action, and the water-resistant and oil-resistant properties of the coating are enhanced.
It significantly improves the waterproof and oil-proof performance and mechanical strength of the coating, improves the permeability and weather resistance of the coating, and solves the problem of poor oil-proof and waterproof performance of existing coatings.
Smart Images

Figure BDA0005151142390000151 
Figure BDA0005151142390000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a highly oil-proof and waterproof fluorine-containing composition and application thereof in coatings. Background Art
[0002] Superhydrophobicity is a surface property of a material, which is reflected in the fact that droplets are not easy to spread, adhere and remain on the surface of the material. This property can be applied to many engineering and technical fields such as self-cleaning, anti-corrosion, hull drag reduction, anti-icing, etc., and has broad application prospects. The hydrophobicity of the material surface is mainly determined by the surface atomic properties and microscopic morphology. Most natural superhydrophobic materials have two characteristics: low interfacial atomic surface energy and micron and nanometer dual-scale rough surface morphology. The contact angle is one of the important criteria for measuring the hydrophobicity of the material surface. It is generally believed that when the contact angle is greater than 150°, the material surface is superhydrophobic.
[0003] Existing super-hydrophobic surface preparation technology such as sol-gel method, vapor deposition method, etching method, template method, anodization method, phase separation, etc., has a complex preparation process and demanding conditions. Super-hydrophobic coating is increasingly used in super-hydrophobic field because of its unique advantages such as simple preparation process, convenient application, wide range of applications. However, existing super-hydrophobic coatings on the market generally have mechanical properties such as strength and substrate adhesion, anti-liquid flow penetration, poor corrosion resistance, etc., which are specifically embodied in coating surface special morphology, easy to fall off, damage, such as encountering high-speed liquid flow impact, prone to penetration damage, easily eroded by acid (base) substances under special environment, and then lose super-hydrophobic performance, and these technical problems make super-hydrophobic coating difficult to large-scale application so far. For example, patent publication number CN201410456523.7 relates to a zinc-aluminum composite coating, including two components A and B. Component A is a two-component composition mixed by components A and B. Component A in component A includes polyarylethersulfoneketone modified resin, silicon carbide micropowder, graphite fluoride and coupling agent component, component B in component A includes silicon carbide, aluminum oxide, solvent, 0.8-6 parts of zinc oxide and epoxy resin component, and component B includes curing agent, defoaming agent and leveling agent. The zinc-aluminum composite coating of the invention has excellent properties such as good wear resistance, mechanical properties, high temperature resistance, flame retardancy, radiation resistance, hydrolysis resistance, insulation stability, etc. The construction process of the zinc-aluminum composite coating is simple and the cost is low, so that the bonding between the zinc-aluminum composite coating and the steel body is strong, and the steel body is well protected from corrosion. However, the main resin of this composite coating is modified with polyarylethersulfoneketone, which has no weather resistance and is prone to yellowing and powdering when exposed to ultraviolet rays or sunlight; and this composite coating is relatively hydrophilic, resulting in poor anti-corrosion performance of the composite coating. Summary of the invention
[0004] In view of this, the present invention proposes a highly oil-proof and water-proof fluorine-containing composition and its application in coatings to solve the problem that the coatings in the prior art have poor oil-proof and water-proof properties, resulting in reduced anti-corrosion performance.
[0005] The technical solution of the present invention is achieved as follows: The present invention provides a highly oil-proof and waterproof fluorine-containing composition, which comprises the following chemical components by weight: 70-80 parts of a resin mixture, 2-5 parts of a diisocyanate, 5-8 parts of a modified titanium dioxide filler and 10-15 parts of a modified glass flake, and the resin mixture comprises a fluorinated hydroxyl acrylic resin and a polyurethane acrylate.
[0006] On the basis of the above technical solution, preferably, in the resin mixture, the mass ratio of the fluorinated hydroxyl acrylic resin to the polyurethane acrylate is 3-5:1.
[0007] Specifically, fluorinated hydroxyl acrylic resin achieves oil and water repellency through the low surface energy characteristics provided by its fluorine-containing groups; polyurethane acrylate provides excellent mechanical strength, flexibility and substrate adhesion; modified titanium dioxide filler forms a strong interface bond with the resin matrix through multiple surface modifications, and the hydrophobic groups on its surface synergize with the fluorine-containing groups in the resin to enhance the overall water and oil repellency effect; modified glass flakes form an orderly arranged layered structure in the coating and are tightly combined with the resin matrix, and the multifunctional groups grafted on its surface not only enhance the compatibility with the substrate, but also improve the overall strength of the coating through entanglement with the resin molecular chains, and the layered structure synergizes with the resin matrix to form an effective anti-penetration barrier.
[0008] On the basis of the above technical solution, preferably, the preparation method of the modified titanium dioxide filler comprises the following steps:
[0009] (1) dispersing titanium dioxide particles in water, then adding sodium silicate solution, stirring evenly, adding acid for aging, and obtaining titanium dioxide coated with silicon dioxide;
[0010] (2) dispersing the titanium dioxide coated with silicon dioxide in an ethanol-water mixed solution, adding a mercaptosilane coupling agent, stirring for reaction, and after the reaction is completed, filtering, washing, and drying to obtain mercapto titanium dioxide;
[0011] (3) Adding mercapto-modified titanium dioxide into DMF, followed by adding trifluoromethylacrylate and benzophenone, and carrying out mercapto-ene reaction under the action of ultraviolet light to obtain modified titanium dioxide filler.
[0012] Titanium dioxide has good chemical stability and weather resistance, which can improve the overall durability of the coating; at the same time, it has certain photocatalytic activity, which can improve the self-cleaning performance of the coating. In step (1), a silicon dioxide coating layer is formed on the surface of titanium dioxide by hydrolysis of sodium silicate to provide active sites. At the same time, the silicon dioxide layer can reduce the photocatalytic activity of titanium dioxide and avoid photodegradation of the resin; in step (2), a mercaptosilane coupling agent is chemically bonded to the surface silicon dioxide layer to introduce active mercapto groups; in step (3), a hydrophobic group is introduced by reacting the mercapto group with trifluoromethylacrylic acid. Not only is the dispersibility of the filler in the resin matrix improved, but the overall waterproof and oil-proof performance of the coating is also enhanced by the introduction of surface hydrophobic groups, while the interfacial bonding between the filler and the resin matrix is improved.
[0013] On the basis of the above technical solution, preferably, in step (1), the mass ratio of titanium dioxide to sodium silicate is 1:0.4-0.8, the aging temperature is 70-90° C., and the aging time is 3-5 h.
[0014] On the basis of the above technical scheme, preferably, the particle size of titanium dioxide particles is 20-1000nm, the concentration of sodium silicate solution is 25-30wt%, the modulus of sodium silicate solution is 2.1-2.4, the acid is preferably a sulfuric acid solution or a hydrochloric acid solution, the acid concentration is 1-2mol / L, and the pH value of the mixed slurry is adjusted to 5-6 by adding acid.
[0015] On the basis of the above technical scheme, preferably, in step (2), the mass ratio of the mercaptosilane coupling agent to the titanium dioxide coated with silicon dioxide is 1:0.8-1.5, the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane, the heating reaction temperature is 70-80°C, the heating reaction time is 2-4h, and the volume ratio of ethanol to water in the ethanol-water mixed solution is 20-30:1.
[0016] Based on the above technical solution, preferably, in step (3), the mass ratio of thiolated titanium dioxide, trifluoromethylacrylate and diphenylacetone is 10-20:1.5-2.5:0.1-0.3, the temperature of the thiolation reaction is 40-50°C, and the reaction time is 20-30min.
[0017] On the basis of the above technical solution, preferably, the preparation method of the modified glass flakes is as follows:
[0018] (a) mixing glass flakes with anhydrous ethanol, stirring for 20-30 minutes, then adding an ethanol solution of γ-aminopropyltrimethoxysilane, stirring at 55-65° C. for 1-3 hours to obtain amino glass flakes;
[0019] (b) adding the amino glass flakes to toluene, adding acryloyl chloride under nitrogen protection, stirring and reacting for 10-20 minutes, adding triethylamine, stirring and reacting at room temperature for 16-20 hours, and obtaining acylated glass flakes;
[0020] (c) The acylated glass flakes are dispersed in DMF, and acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxytetrayl] ethyl methacrylate are added and stirred to mix evenly. Then, azobisisobutyronitrile is added and a graft copolymerization reaction is carried out at room temperature under ultraviolet light for 2-3 hours to obtain modified glass flakes.
[0021] Specifically, the reactive sites are first constructed on the surface through amination, followed by the introduction of polymerizable double bonds through acylation, and finally a variety of functional groups are introduced through graft copolymerization, among which the carboxyl group is introduced into the acrylic monomer to provide reactive sites, the hydrophobic and oil-proof groups are introduced into perfluorooctyl ethyl acrylate, and the 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyteayl] ethyl methacrylate provides UV protection. Through multiple modifications, not only the compatibility of the glass flakes with the resin matrix is improved, but also multiple functions such as hydrophobic and oil-proof and UV resistance are given to it, so that the modified glass flakes can play a synergistic role of enhancement and protection in the coating.
[0022] Based on the above technical scheme, preferably, in step (a), the mass ratio of glass flakes and γ-aminopropyltrimethoxysilane is 100:10-15, and the mass concentration of the ethanol solution of γ-aminopropyltrimethoxysilane is 5-7%; in step (b), the mass ratio of amino glass flakes, acryloyl chloride and triethylamine is 100:8-12:12-15.
[0023] On the basis of the above technical scheme, preferably, in step (c), the mass ratio of the acylated glass flakes to the total mass of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxypropyl]methacrylate is 100:20-25; the mass ratio of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxypropyl]methacrylate is 1:2:1; and the amount of azobisisobutyronitrile added is 2-3% of the total mass of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxypropyl]methacrylate.
[0024] On the basis of the above technical solution, preferably, the diisocyanate is isophorone diisocyanate or toluene diisocyanate.
[0025] The present invention provides a method for preparing a highly oil-proof and waterproof fluorine-containing composition as described in any one of the above items, comprising the following steps:
[0026] S1, mixing and dispersing the fluorinated hydroxyl acrylic resin and the polyurethane acrylate in ethyl acetate in a mass ratio of 3-5:1, and stirring to obtain a resin mixture;
[0027] S2. Add modified titanium dioxide filler and modified glass flakes to the resin mixture in sequence, and stir and disperse at 35-45°C for 30-60 minutes; then add diisocyanate, stir evenly for 10-20 minutes, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0028] Specifically, the -NCO group in the diisocyanate molecule can react with the hydroxyl group in the resin body, the carboxyl group on the surface of the modified titanium dioxide filler, and the carboxyl group on the surface of the modified glass flakes, thereby firmly fixing the modified titanium dioxide filler and the modified glass flakes in the network structure through chemical bonding, enhancing the interfacial bonding force between the components and improving the overall mechanical strength and durability of the anti-fluorine composition.
[0029] The present invention provides the use of a highly oil-proof and waterproof fluorine-containing composition as described above in a coating, which comprises 60-70 parts of the fluorine-containing composition, 0.5-1.0 parts of a leveling agent and 15-20 parts of ethyl acetate in parts by weight.
[0030] The highly oil-proof and waterproof fluorine-containing composition of the present invention and its application in coatings have the following beneficial effects compared with the prior art:
[0031] (1) Fluorinated hydroxyl acrylic resin provides basic waterproof and oil-proof properties, while polyurethane acrylate provides mechanical strength and toughness, and the two are compounded to achieve complementary performance; modified titanium dioxide filler improves the compatibility and interfacial bonding with the resin matrix through multiple surface modifications, while enhancing the overall protective performance of the coating; modified glass flakes form an orderly arranged layered structure in the coating, significantly improving the coating's anti-permeability and weather resistance; diisocyanate forms a dense three-dimensional network structure through cross-linking reactions with the hydroxyl groups in the resin molecules and the active groups on the filler surface, further enhancing the overall performance of the coating; the various components form a stable composite structure through chemical bonding and physical action, ultimately allowing the fluorine-containing composition to exhibit excellent waterproof and oil-proof properties and good mechanical strength;
[0032] (2) A silicon dioxide layer is formed by coating with sodium silicate, and then a mercaptosilane coupling agent is introduced for the first step of surface modification. Finally, a fluorine group is further introduced through a mercapto-ene reaction. This layer-by-layer construction strategy forms a functionalized interface layer with a gradient transition on the surface of the filler. Titanium dioxide as a core filler has excellent weather resistance and light stability. The surface-coated silicon dioxide layer not only provides abundant surface hydroxyl groups for subsequent modification, but also effectively prevents direct contact between titanium dioxide and the resin matrix, thereby avoiding photocatalytic degradation. The mercapto group provides an active site for chemical bonding with the resin matrix, and the fluorine-containing group gives the filler excellent hydrophobic properties, significantly improving the dispersion stability of the filler and its compatibility with the resin matrix, thereby increasing the waterproof and oil-proof properties of the resin mixture.
[0033] (3) In the modified glass flakes, they are first aminated with γ-aminopropyltrimethoxysilane to form a uniform amino active layer on the surface of the glass flakes; then they are acylated with acryloyl chloride to convert the surface amino groups into amide structures containing unsaturated double bonds, providing reaction sites for further functionalization; finally, through a graft copolymerization reaction initiated by ultraviolet light, an acrylic skeleton, a perfluorooctyl hydrophobic group and a benzotriazole UV protective group are simultaneously introduced into the surface of the glass flakes, so that the modified glass flakes can not only form an effective layered barrier structure in the coating, but also significantly improve the anti-permeability, hydrophobicity and weather resistance of the coating through the synergistic effect of the surface functional groups. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that
[0036] Polyurethane acrylate was purchased from Ruisheng New Materials Co., Ltd. with a product brand of RU-6380H and a viscosity of 1500-3000 cps / 25°C; titanium dioxide was purchased from Shanghai Yunfu Nanotechnology Co., Ltd.
[0037] In the embodiment of the present application, the fluorinated hydroxyl acrylic resin is prepared by the following method. Specifically, the preparation method is:
[0038] 5% to 8% by mass of methyl methacrylate (MMA), 35% to 50% by mass of n-butyl acrylate (BA), 3.5% to 5.5% by mass of hydroxyethyl methacrylate (HEMA), 30% to 45% by mass of methacrylic acid (MAA), 15% to 20% by mass of dodecafluoroheptyl methacrylate (G04) monomer, 1.5% to 2% by mass of mercaptoethanol as a chain transfer agent, and 1% to 1.5% by mass of tert-butyl peroxide (TBPB) as an initiator are mixed to obtain a mixed solution;
[0039] Using tert-butyl carbonate (E10P) and propylene glycol butyl ether in a mass ratio of 1:1 as a solvent, wherein the mass of the solvent is 15% to 25% of the total mass of the monomers;
[0040] Add solvent to the reaction container, introduce nitrogen, stir and heat to 140-160°C, add 10-15% of the mixed solution of monomer, chain transfer agent and initiator at one time, react for 30 minutes, add the remaining mixed solution dropwise at a uniform speed within 6-7 hours, keep warm for 0.5 hours, then add 0.5% of initiator, keep warm for 1-1.5 hours to terminate the polymerization, cool to 70-90°C, neutralize with N,N-dimethylethanolamine, add water and disperse at high speed to obtain fluorinated hydroxy acrylic resin.
[0041] Example 1
[0042] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0043] S1, 80g of fluorinated hydroxyl acrylic resin and 20g of polyurethane acrylate were mixed to obtain a resin mixture, and then 75g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0044] S2. Add 6.5 g of modified titanium dioxide filler and 13 g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 40°C for 45 min; then add 3.5 g of diisocyanate, stir evenly for 15 min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0045] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0046] (1) 40 g of titanium dioxide particles with a particle size of 500 nm were dispersed in 100 ml of water, and then 24 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 1.5 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 80° C. for 4 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0047] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 12 g of titanium dioxide coated with silicon dioxide in 150 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 25:1), heating and stirring at 75° C. for 3 h, filtering, washing, and drying after the reaction is completed to obtain mercapto titanium dioxide;
[0048] (3) 15 g of mercapto titanium dioxide was added to 150 ml of DMF, followed by 2 g of trifluoromethylacrylic acid and 0.2 g of benzophenone. 2 ) to carry out mercapto-ene reaction at a reaction temperature of 45° C. for a reaction time of 25 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0049] The preparation method of modified glass flakes is as follows:
[0050] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and the mixture was dispersed by ultrasonic stirring for 25 min. Then, 1.3 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 6%) was added, and the mixture was stirred at 60° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-treated glass flakes.
[0051] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 1.0 g of acryloyl chloride under nitrogen protection, stir and react for 15 min, then add 1.35 g of triethylamine, stir and react at room temperature for 18 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0052] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 5.8 g of acrylic acid monomer, 5.8 g of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxytetrazolyl]ethyl methacrylate and 11.5 g of perfluorooctyl ethyl acrylate in sequence, stir and mix evenly, then dissolve 0.6 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction at room temperature under ultraviolet light (wavelength 365 nm) for 2.5 hours. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0053] Example 2
[0054] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0055] S1, 75g of fluorinated hydroxyl acrylic resin and 25g of polyurethane acrylate were mixed to obtain a resin mixture, and then 70g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0056] S2. Add 5g of modified titanium dioxide filler and 10g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 35°C for 60min; then add 2g of diisocyanate, stir evenly for 10min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0057] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0058] (1) 40 g of titanium dioxide particles with a particle size of 100 nm were dispersed in 100 ml of water, and then 16 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. 1 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 70° C. for 5 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0059] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 8 g of titanium dioxide coated with silicon dioxide in 100 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 20:1), heating and stirring at 70° C. for 4 h, and filtering, washing, and drying after the reaction to obtain mercapto titanium dioxide;
[0060] (3) 10 g of mercapto titanium dioxide was added to 100 ml of DMF, followed by 1.5 g of trifluoromethylacrylic acid and 0.1 g of benzophenone. The mixture was stirred under ultraviolet light (ultraviolet light intensity was 550 mW / cm 2 ) to carry out mercapto-ene reaction at a reaction temperature of 40° C. for a reaction time of 30 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0061] The preparation method of modified glass flakes is as follows:
[0062] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and the mixture was dispersed by ultrasonic stirring for 20 min. Then, 1 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 5%) was added, and the mixture was stirred at 55° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-treated glass flakes.
[0063] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 0.8 g of acryloyl chloride under nitrogen protection, stir and react for 10 min, then add 1.2 g of triethylamine, stir and react at room temperature for 16 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0064] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 5 g of acrylic acid monomer, 5 g of 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxytetrazolyl]ethyl methacrylate and 10 g of perfluorooctyl ethyl acrylate in sequence, stir and mix evenly, then dissolve 0.4 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction at room temperature under ultraviolet light (wavelength 365 nm) for 2 h. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0065] Example 3
[0066] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0067] S1, 83g of fluorinated hydroxyl acrylic resin and 17g of polyurethane acrylate were mixed to obtain a resin mixture, and then 80g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0068] S2. Add 8g of modified titanium dioxide filler and 15g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 45°C for 30min; then add 5g of diisocyanate, stir evenly for 20min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0069] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0070] (1) 40 g of titanium dioxide particles with a particle size of 1000 nm were dispersed in 100 ml of water, and then 32 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 2 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 90° C. for 3 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0071] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 15 g of titanium dioxide coated with silicon dioxide in 200 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 20:1), heating and stirring at 80° C. for 2 h, and filtering, washing, and drying after the reaction is completed to obtain mercapto titanium dioxide;
[0072] (3) 20 g of mercapto titanium dioxide was added to 200 ml of DMF, followed by 2.5 g of trifluoromethylacrylic acid and 0.3 g of benzophenone. The mixture was stirred under ultraviolet light (ultraviolet light intensity was 550 mW / cm 2 ) to carry out mercapto-ene reaction at a reaction temperature of 50° C. for a reaction time of 20 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0073] The preparation method of modified glass flakes is as follows:
[0074] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and dispersed by ultrasonic stirring for 20-30 min, and then 1.5 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 5-7%) was added, and stirred at 65° C. for 1 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino glass flakes;
[0075] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 1.2 g of acryloyl chloride under nitrogen protection, stir and react for 20 min, then add 1.5 g of triethylamine, stir and react at room temperature for 20 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0076] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 6.25 g of acrylic acid monomer, 6.25 g of 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxytetrazolyl]ethyl methacrylate and 12.5 g of perfluorooctyl ethyl acrylate in sequence, stir and mix evenly, then dissolve 0.75 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction at room temperature under ultraviolet light (wavelength 365 nm) for 3 hours. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0077] Example 4
[0078] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0079] S1, 77g of fluorinated hydroxyl acrylic resin and 23g of polyurethane acrylate were mixed to obtain a resin mixture, and then 73g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0080] S2. Add 6 g of modified titanium dioxide filler and 11.5 g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 40°C for 50 min; then add 3 g of diisocyanate, stir evenly for 18 min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0081] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0082] (1) 40 g of titanium dioxide particles with a particle size of 800 nm were dispersed in 100 ml of water, and then 20 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 1.5 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 75° C. for 4.5 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0083] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 10 g of titanium dioxide coated with silicon dioxide in 150 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 25:1), heating and stirring at 75° C. for 2.5 h, filtering, washing, and drying after the reaction is completed to obtain mercapto titanium dioxide;
[0084] (3) 12 g of mercapto titanium dioxide was added to 120 ml of DMF, followed by 1.8 g of trifluoromethylacrylic acid and 0.25 g of benzophenone. 2 ) to carry out mercapto-ene reaction at a reaction temperature of 45° C. for a reaction time of 22 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0085] The preparation method of modified glass flakes is as follows:
[0086] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and the mixture was dispersed by ultrasonic stirring for 25 min. Then, 1.2 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 6%) was added, and the mixture was stirred at 60° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-treated glass flakes.
[0087] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 1.1 g of acryloyl chloride under nitrogen protection, stir and react for 15 min, then add 1.3 g of triethylamine, stir and react at room temperature for 19 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0088] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 6 g of acrylic acid monomer, 6 g of 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxytetrazolyl]ethyl methacrylate and 11 g of perfluorooctyl ethyl acrylate in sequence, stir and mix evenly, then dissolve 0.6 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction at room temperature under ultraviolet light (wavelength 365 nm) for 2.5 hours. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0089] Comparative Example 1
[0090] This comparative example discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0091] S1, 80g of fluorinated hydroxyl acrylic resin and 20g of polyurethane acrylate were mixed to obtain a resin mixture, and then 75g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0092] S2. Add 6.5 g of modified titanium dioxide filler and 13 g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 40°C for 45 min; then add 3.5 g of diisocyanate, stir evenly for 15 min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0093] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0094] (1) 40 g of titanium dioxide particles with a particle size of 500 nm were dispersed in 100 ml of water, and then 24 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 1.5 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 80° C. for 4 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide, i.e., modified titanium dioxide filler;
[0095] The preparation method of modified glass flakes is as follows:
[0096] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and the mixture was dispersed by ultrasonic stirring for 25 min. Then, 1.3 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 6%) was added, and the mixture was stirred at 60° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-treated glass flakes.
[0097] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 1.0 g of acryloyl chloride under nitrogen protection, stir and react for 15 min, then add 1.35 g of triethylamine, stir and react at room temperature for 18 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0098] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 5.8 g of acrylic acid monomer, 5.8 g of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxytetrazolyl]ethyl methacrylate and 11.5 g of perfluorooctyl ethyl acrylate in sequence, stir and mix evenly, then dissolve 0.6 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction at room temperature under ultraviolet light (wavelength 365 nm) for 2.5 hours. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0099] Comparative Example 2
[0100] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0101] S1, 80g of fluorinated hydroxyl acrylic resin and 20g of polyurethane acrylate were mixed to obtain a resin mixture, and then 75g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0102] S2. Add 6.5 g of modified titanium dioxide filler and 13 g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 40°C for 45 min; then add 3.5 g of diisocyanate, stir evenly for 15 min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0103] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0104] (1) 40 g of titanium dioxide particles with a particle size of 500 nm were dispersed in 100 ml of water, and then 24 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 1.5 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 80° C. for 4 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0105] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 12 g of titanium dioxide coated with silicon dioxide in 150 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 25:1), heating and stirring at 75° C. for 3 h, filtering, washing, and drying after the reaction is completed to obtain mercapto titanium dioxide;
[0106] (3) 15 g of mercapto titanium dioxide was added to 150 ml of DMF, followed by 2 g of trifluoromethylacrylic acid and 0.2 g of benzophenone. 2 ) to carry out mercapto-ene reaction at a reaction temperature of 45° C. for a reaction time of 25 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0107] The preparation method of modified glass flakes is as follows:
[0108] (1) Mix 10 g of glass flakes with 200 ml of anhydrous ethanol, disperse under ultrasonic stirring for 25 min, then add 1.3 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane is prepared as an ethanol solution with a mass concentration of 6%), stir at 60°C for 2 h, and after the reaction is completed, filter, wash, and dry to obtain amino glass flakes.
[0109] Comparative Example 3
[0110] This embodiment discloses a highly oil-proof and waterproof fluorine-containing composition and a preparation method thereof, comprising the following steps:
[0111] S1, 80g of fluorinated hydroxyl acrylic resin and 20g of polyurethane acrylate were mixed to obtain a resin mixture, and then 75g of the resin mixture was dispersed in 700ml of ethyl acetate and stirred to obtain a resin mixture;
[0112] S2. Add 6.5 g of modified titanium dioxide filler and 13 g of modified glass flakes to the resin mixture in sequence, and stir and disperse at 40°C for 45 min; then add 3.5 g of diisocyanate, stir evenly for 15 min, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
[0113] Wherein, the preparation method of modified titanium dioxide filler is as follows:
[0114] (1) 40 g of titanium dioxide particles with a particle size of 500 nm were dispersed in 100 ml of water, and then 24 g of sodium silicate solution (the concentration of the sodium silicate solution was 30 wt%) was added, and the mixture was stirred evenly. A 1.5 mol / L sulfuric acid solution was added to adjust the pH to 5-6, and the mixture was aged at 80° C. for 4 h, and then filtered, washed, and dried in sequence to obtain titanium dioxide coated with silicon dioxide;
[0115] (2) dispersing 10 g of 3-mercaptopropyltrimethoxysilane and 12 g of titanium dioxide coated with silicon dioxide in 150 ml of an ethanol-water mixed solution (the volume ratio of ethanol to water is 25:1), heating and stirring at 75° C. for 3 h, filtering, washing, and drying after the reaction is completed to obtain mercapto titanium dioxide;
[0116] (3) 15 g of mercapto titanium dioxide was added to 150 ml of DMF, followed by 2 g of trifluoromethylacrylic acid and 0.2 g of benzophenone. 2 ) to carry out mercapto-ene reaction at a reaction temperature of 45° C. for a reaction time of 25 min, and after the reaction is completed, filtering, washing and drying to obtain a modified titanium dioxide filler;
[0117] The preparation method of modified glass flakes is as follows:
[0118] (1) 10 g of glass flakes were mixed with 200 ml of anhydrous ethanol, and the mixture was dispersed by ultrasonic stirring for 25 min. Then, 1.3 g of γ-aminopropyltrimethoxysilane (γ-aminopropyltrimethoxysilane was prepared as an ethanol solution with a mass concentration of 6%) was added, and the mixture was stirred at 60° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-treated glass flakes.
[0119] (2) Add 10 g of amino glass flakes to 100 ml of toluene, ultrasonically disperse for 10 min, add 1.0 g of acryloyl chloride under nitrogen protection, stir and react for 15 min, then add 1.35 g of triethylamine, stir and react at room temperature for 18 h, filter, wash and dry after the reaction is completed to obtain acylated glass flakes;
[0120] (3) Disperse 10 g of acylated glass flakes in 100 ml of DMF, add 11.5 g of perfluorooctyl ethyl acrylate in turn, stir and mix evenly, then dissolve 0.6 g of azobisisobutyronitrile in 10 ml of DMF, slowly add it dropwise to the reaction system, and carry out graft copolymerization reaction under ultraviolet light (wavelength 365 nm) at room temperature for 2.5 hours. After the reaction is completed, filter, wash and dry to obtain modified glass flakes.
[0121] Preparation of coatings
[0122] 65 g of the fluorine-containing composition prepared in the examples and comparative examples was weighed and dispersed in 20 g of toluene, stirred evenly, and 0.8 g of a leveling agent (polyether-modified fluorosilicone oil, product brand TPD-FS8013) was added to obtain a coating.
[0123] Performance Testing
[0124] After the coatings prepared in the examples and comparative examples were sprayed onto a glass substrate and cured to obtain a coating, the performance of the coating was tested, including the hydrophobic angle and the oleophobic angle. After being adhered and compacted with 3M tape, the coating was pulled upward at a 45° angle horizontally. This was repeated 100 times, and the hydrophobic angle and the oleophobic angle were measured using a ZR-SDJ-QH6 contact angle meter. The test results are shown in Table 1.
[0125] Table 1 Hydrophobic angle and oleophobic angle
[0126]
[0127]
[0128] The stain resistance, adhesion and wear resistance of the coatings prepared in the examples and comparative examples were tested. The adhesion test method was as follows: the adhesion performance of the coating was tested by the pull-off method, see GB / T5210-2006 "Pull-off adhesion test for paint and varnish". Wear resistance test method: the test was conducted by using a steel wool abrasion tester, using 0000# steel wool, an area of 10×10mm, a stroke of 40 times / min, a load of 100g, and the water contact angle of the test piece was tested every 100 frictions. When the water contact angle was less than 150°, the test was stopped and the final number was recorded; stain resistance: chili oil was applied to the surface of the coating to be tested, and after standing for 1 hour, it was observed whether it could be wiped off; level 1 represented complete wiping without residue, level 2 represented a light trace of about 30%, and level 3 represented obvious traces, with a trace area of >30%. The specific test results are shown in Table 2.
[0129] Table 2 Stain resistance, adhesion and wear resistance
[0130] Adhesion(MPa) Wear resistance (times) Stain resistance Example 1 7.25 3800 Level 1 Example 2 6.95 3400 Level 1 Example 3 7.38 3600 Level 1 Example 4 7.08 3500 Level 1 Comparative Example 1 3.57 3100 Level 2 Comparative Example 2 4.08 2800 Level 2 Comparative Example 3 6.59 3200 Level 2
[0131] As can be seen from Tables 1 and 2, the fluorine-containing composition prepared by the preparation method of the present invention is obtained by compounding the modified titanium dioxide filler with a resin mixture and a photoinitiator, and then applying it to a coating to obtain a coating surface with super hydrophobic and oleophobic properties, which can significantly improve the waterproof and oil-proof properties of the coating.
[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly oil-proof and waterproof fluorine-containing composition, characterized in that: In parts by weight, the fluorine-containing composition includes the following chemical components: 70-80 parts of a resin mixture, 2-5 parts of a diisocyanate, 5-8 parts of a modified titanium dioxide filler and 10-15 parts of a modified glass flake. The resin mixture includes a fluorinated hydroxyl acrylic resin and a polyurethane acrylate, and the mass ratio of the fluorinated hydroxyl acrylic resin to the polyurethane acrylate is 3-5:
1.
2. A highly oil-proof and waterproof fluorine-containing composition according to claim 1, characterized in that: The preparation method of the modified titanium dioxide filler comprises the following steps: (1) dispersing titanium dioxide particles in water, then adding sodium silicate solution, stirring evenly, adding acid for aging, and obtaining titanium dioxide coated with silicon dioxide; (2) dispersing the titanium dioxide coated with silicon dioxide in an ethanol-water mixed solution, adding a mercaptosilane coupling agent, stirring for reaction, and after the reaction is completed, filtering, washing, and drying to obtain mercapto titanium dioxide; (3) Adding mercapto-modified titanium dioxide into DMF, followed by adding trifluoromethylacrylate and benzophenone, and carrying out mercapto-ene reaction under the action of ultraviolet light to obtain modified titanium dioxide filler.
3. A highly oil-proof and waterproof fluorine-containing composition as claimed in claim 2, characterized in that: In step (1), the mass ratio of titanium dioxide to sodium silicate is 1:0.4-0.8, the aging temperature is 70-90°C, and the aging time is 3-5h; in step (2), the mass ratio of the mercaptosilane coupling agent to the titanium dioxide coated with silicon dioxide is 1:0.8-1.5, the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane, the heating reaction temperature is 70-80°C, and the heating reaction time is 2-4h.
4. A highly oil-proof and waterproof fluorine-containing composition as claimed in claim 2, characterized in that: In step (3), the mass ratio of thiolated titanium dioxide, trifluoromethylacrylic acid and diphenylacetone is 10-20:1.5-2.5:0.1-0.3, the temperature of the thiolation reaction is 40-50° C., and the reaction time is 20-30 min.
5. A highly oil-proof and waterproof fluorine-containing composition according to claim 1, characterized in that: The preparation method of the modified glass flakes is as follows: (a) mixing glass flakes with anhydrous ethanol, stirring for 20-30 minutes, then adding an ethanol solution of γ-aminopropyltrimethoxysilane, stirring at 55-65° C. for 1-3 hours, to obtain amino glass flakes; (b) adding the amino glass flakes to toluene, adding acryloyl chloride under nitrogen protection, stirring and reacting for 10-20 minutes, adding triethylamine, stirring and reacting at room temperature for 16-20 hours, and obtaining acylated glass flakes; (c) The acylated glass flakes are dispersed in DMF, and acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-phenyltriazole-2-yl)-4-hydroxytetrayl] ethyl methacrylate are added and stirred to mix evenly. Then, azobisisobutyronitrile is added and a graft copolymerization reaction is carried out at room temperature under ultraviolet light for 2-3 hours to obtain modified glass flakes.
6. A highly oil-proof and waterproof fluorine-containing composition according to claim 5, characterized in that: In step (a), the mass ratio of glass flakes to γ-aminopropyltrimethoxysilane is 100:10-15, and the mass concentration of the ethanol solution of γ-aminopropyltrimethoxysilane is 5-7%; in step (b), the mass ratio of amino glass flakes, acryloyl chloride and triethylamine is 100:8-12:12-15.
7. A highly oil-proof and waterproof fluorine-containing composition according to claim 5, characterized in that: In step (c), the mass ratio of the acylated glass flakes to the total mass of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-benzotriazole-2-yl)-4-hydroxytetrayl]ethyl methacrylate is 100:20-25; the mass ratio of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-benzotriazole-2-yl)-4-hydroxytetrayl]ethyl methacrylate is 1:2:1; and the amount of azobisisobutyronitrile added is 2-3% of the total mass of acrylic acid monomer, perfluorooctyl ethyl acrylate and 2-[3-(2H-benzotriazole-2-yl)-4-hydroxytetrayl]ethyl methacrylate.
8. A highly oil-proof and waterproof fluorine-containing composition according to claim 1, characterized in that: The diisocyanate is isophorone diisocyanate or toluene diisocyanate.
9. A method for preparing a highly oil-proof and waterproof fluorine-containing composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing and dispersing the fluorinated hydroxyl acrylic resin and the polyurethane acrylate in ethyl acetate in a mass ratio of 3-5:1, and stirring to obtain a resin mixture; S2. Add modified titanium dioxide filler and modified glass flakes to the resin mixture in sequence, and stir and disperse at 35-45°C for 30-60 minutes; then add diisocyanate, stir evenly for 10-20 minutes, and finally adjust the solid content to 30-35% to obtain a highly oil-proof and waterproof fluorine-containing composition.
10. Use of the highly oil-proof and waterproof fluorine-containing composition according to any one of claims 1 to 8 in coatings.
Citation Information
Patent Citations
A kind of zinc-aluminum composite coating and construction technology thereof
CN104177986B
Coating and glazing process for inorganic decorative sheets and preparation method of coatings
CN107286817A
Two-component waterborne polyurethane coating as well as preparation method and application thereof
CN112322170A
Water-based fluorine-containing polyurethane acrylate coating as well as preparation method and application thereof
CN112521841A
Electromagnetic shielding filler, electromagnetic shielding coating comprising the same, preparation method and use thereof
US20210122940A1
Cited By
Wear-resistant anti-aging polyurethane resin and preparation method thereof
CN120059121A
Fluorine-free bio-based membrane transfer oil-proof paper as well as preparation method and application thereof
CN120331067A
Waterborne polyurethane composite material as well as preparation method and application thereof
CN121005862A